Urgent needs in fostering neglected tropical diseases (NTDs) laboratory capacity in WHO Western Pacific Region: results from the external quality assessment on NTDs diagnosis in 2012-2015 - Yan Lu; Glenda Gonzales; Shao-Hong Chen; Hao Li; Yu-Chun Cai; Yan-Hong Chu; Lin Ai; Mu-Xin Chen; Hai-Ning Chen; Jia-Xu Chen (BMC, 2017)
Abstract Background Neglected tropical diseases (NTDs) are a heterogeneous group of mainly chronic, debilitating and often stigmatizing diseases that largely affects low-income and politically marginalized populations, causing a large burden of public health, social and economies in the NTDs endemic countries. NTDs are caused by infections with a range of pathogen, including bacteria, parasites, protozoa and viruses. The accurate diagnosis of NTDs is important for reducing morbidity, preventing mortality and for monitoring of control programs. External Quality Assessment (EQA), a component of laboratory quality assurance, aims to assess the performance of participating laboratories in detecting parasitic infections. The aim of this paper is to report the findings and put forward the recommendations on capacity build from the EQA results of participating NTDs laboratories in selected countries in the WHO Western Pacific Region from 2012 to 2015. Methods Reference or public health laboratories at national level working on NTDs in 6 countries participated in EQAs organized by the National Institute of Parasitic Diseases (NIPD) of Chinese Center for Disease Control and Prevention (CDC) based in Shanghai, China. Two representatives of each participating laboratory were invited to NIPD to detect NTDs' parasitic infections using the same prepared samples for serological tests (IHA and ELISA) and helminth eggs' morphological tests (Direct smear and Kato-Katz). All of the results were scored and analyzed by using SPSS statistics 19.0 software. Results The percentage of participants who had EQA score ≥ 60 during 2012-2015 for direct smear test were 80.00% (2012), 71.43% (2013), 100% (2014) and 75.00% (2015), whereas for Kato-Katz test were 80.00% (2012), 57.14% (2013), 100% (2014) and 37.50% (2015), respectively. The detection rate of helminth eggs varied in different species, with Ascaris lumbricoides being the highest at 94.07% in average. All laboratories did very well with ELISA tests as shown by the high scores in all four years except Lab A in the first and last EQA. For the positive or negative judgments of serum samples, the total coincidence rates of ELISA between 2012 and 2015 were 90.00%, 99.29%, 94.29% and 98.75%, respectively. While the total coincidence rates of IHA were respectively 100%, 95.00%, 90.00% and 97.50%. However, detecting low levels of serum antibody remained problematic for IHA when the titres of samples were taken into consideration. Conclusion This study demonstrate that EQA scheme have been beneficial to the participating laboratories. The EQA programme identifies certain deficiencies which were needed to overcome and improved the laboratories' performance in helminthiasis diagnosis. However, further optimization of accuracy and uniformity in NTDs diagnosis remains a big challenge.